Relationship Between Organisational Factors and Adoption of New Technology in Kenya: A Case of CEMASTEA - Ann M. Kisaumbi (European Scientific Journal, ESJ, 2022)
This research evaluated the relationship between organisational factors and adoption of new technology in education support organisations in Kenya based on the case of Centre for Mathematics, Science and Technology Education in Africa (CEMASTEA). The research design adopted for this study was descriptive correlational design. The study population was 214 employees of CEMASTEA. A stratified sample of 64 participants was drawn from the different departments within the institution. A structured questionnaire was developed for data collection. Data was analysed using descriptive statistics and regression analysis in SPSS. An R-Square of 0.749 with the standard error of estimate being 0.235 was found, implying that for any variation in adoption of new technology by one-unit, organisational factors explained 74.9% of such variation. This was a demonstration that organisational factors were a salient determinant of technology adoption success. Government and all relevant authorities should also formulate and implement policies that will assist organisations adopt and adapt to new technologies in a favourable and user-friendly environment.